2023
DOI: 10.1038/s41419-023-05556-y
|View full text |Cite
|
Sign up to set email alerts
|

The U2AF65/circNCAPG/RREB1 feedback loop promotes malignant phenotypes of glioma stem cells through activating the TGF-β pathway

Abstract: Glioma is the most aggressive and common malignant neoplasms in human brain tumors. Numerous studies have showed that glioma stem cells (GSCs)drive the malignant progression of gliomas. Recent studies have revealed that circRNAs can maintain stemness and promote malignant progression of glioma stem cells. We used bioinformatics analysis to identify circRNAs and potential RNA-binding proteins (RBPs) in glioma. qRT-PCR, western blotting, RNA FISH, RNA pull-down, RNA immunoprecipitation assay, ChIP, immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…6C, D ), supporting the idea that acetylation of U2AF2 is responsible for fibrotic reaction under TGF-β1. Additionally, a recent study showed that U2AF2 can directly bind and stabilize circNCAPG, which participates in the nuclear translocation of ras responsive element binding protein 1, thereby activating the TGF-β pathway and promoting glioma progression 47 . Taking this into consideration, we speculate that U2AF2 may be a positive feedback regulator of TGF-β1, although further investigations are required to ascertain this.…”
Section: Discussionmentioning
confidence: 99%
“…6C, D ), supporting the idea that acetylation of U2AF2 is responsible for fibrotic reaction under TGF-β1. Additionally, a recent study showed that U2AF2 can directly bind and stabilize circNCAPG, which participates in the nuclear translocation of ras responsive element binding protein 1, thereby activating the TGF-β pathway and promoting glioma progression 47 . Taking this into consideration, we speculate that U2AF2 may be a positive feedback regulator of TGF-β1, although further investigations are required to ascertain this.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of Miat leads to differentiation of tumorigenic stem‐cell like MB cells and differentiation of tumorigenic stem‐cell like MB cells into a non‐tumorigenic state 76 . Most recently, circular RNAs has also been demonstrated to regulate pluripotency and tumor cell growth in brain tumor, such as circNDC80, circNCAPG, circRPPH1, and circKPNB1 77–80 . Taken together, these findings suggest that ncRNAs not only affect the function of non‐CSCs but also regulate the function of CSCs.…”
Section: Intrinsic Regulators Of Cancer Stemness In Brain Tumormentioning
confidence: 90%
“…Tumor tissue from LUSC patients was xed in 10% formalin at 4°C overnight and embed in para n. 5-µm sections were incubated with primary and secondary antibodies (Abcepta Biotech Ltd. Co.) successively [32] .…”
Section: Immunohistochemistrymentioning
confidence: 99%